Technology transfer of lead-free (K, Na)NbO3-based piezoelectric ceramics. (October 2019) - Thong, Hao-Cheng; Zhao, Chunlin; Zhou, Zhen; Wu, Chao-Feng; Liu, Yi-Xuan; Du, Zong-Zheng; Li, Jing-Feng; Gong, Wen; Wang, Ke
Graphical abstract: Abstract: Piezoelectric materials are an important functional material in the modern world because they are capable of converting electrical energy into mechanical energy and vice versa. Lead-free potassium sodium niobate (KNN)-based piezoelectric materials have been intensively researched in the past decade for only one purpose: to replace the less environmentally friendly lead-based piezoelectric materials in commercial products. In this review, the historical research evolution of KNN-based piezoelectric ceramics is highlighted. Meanwhile, to evaluate the technology transfer status, we emphasize on the analysis of the patents applied within the past five years, as well as certain practical applications of KNN-based materials. This paper concludes with the prediction of remaining challenges and opportunities for adopting the lead-free KNN-based piezoelectric ceramics in practical applications.